Implementation of Markov Chain on MSME Data for QRIS Users in Medan City - Elisabet Desy Yulianawati Hia; Marlina Setia Sinaga (PT FORMOSA CENDEKIA GLOBAL, 2022)
QRIS (Quick Response Indonesian Standard) is a non-cash payment system innovation initiated by Bank Indonesia in collaboration with the Indonesian Payment System Association. This is one response to the era of digitalization and industry 4.0. Since January 2020, Bank Indonesia has required ( implemented) QRIS for non-cash payments, especially for micro, small and medium enterprises (SMEs), because it is a sector that contributes to Gross Domestic Product. Therefore, this study is intended to predict the number of SMEs using QRIS in Medan in the future based on the Markov Chain method. The data used is the number of MSMEs that use QRIS as a cashless payment in Medan City from Bank Indonesia North Sumatra in December 2019 to June 2022. The results show that there is a balance in October 2022 with a 52.2% chance percentage with declining conditions; 30.4% with an increasing condition, and 8.7% with a strongly increasing and decreasing condition. This good accuracy is checked with Mean Absolute Percentage Error (MAPE).